Book Review: Pfeil und Bogen in der Römischen Kaiserzeit, by Holger Riesch - Antje Wilton (EXARC Journal, 2019)
This book closes a gap both in the documentation of the history of the Roman army as well as the history of archery in that it provides a very comprehensive overview on the use of bow and arrow in the Roman Empire. It collects and systematically discusses a wealth of information on a range of topics related to Roman archery in the imperial period and extends that discussion to previous and following periods and to cultural influences outside the Roman Empire where appropriate.